HUBUNGAN KEKUATAN OTOT LENGAN-BAHU DAN KELENTUKAN PUNGGUNG DENGAN SERVIS ATAS BOLA VOLI PADA TIM SMP AZZUHRA PEKANBARU - Rifqi, Muhammad; Zainur, Zainur; Wijayanti, Ni Putu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to determine whether there is a corelation of the shoulder musce strength and the back muscle with the servis of volley ball in the team of azzuhra pekanbaru. The form of this research is correlation research, the population in this study is azzuhra Pekanbaru new junior high school students. The sample in this study were 17 people. The sample technique used is total sampling (saturated sample). thus the sample in this study amounted to 17 people. After that, the data is processed statistically, to test normality using the lilifors test and correlation at a significant level α (0.05). The first analysis between the strength of the shoulder arm muscles (x1) with the service of the volleyball team azzuhra Pekanbaru new team (y). where rtab at a significant level α (0.05) = 0.482 means, rcount (0.628)> rtab (0.482), meaning that the hypothesis is accepted and there is a significant relationship between shoulder arm muscle strength and volleyball service on the Pekanbaru AZZUHRA SMP team. The second analysis between the back muscles (x2), with the service of volleyball azzuhra junior team (Y) was obtained, where rtab at a significant level α (0.05) = 0.482 means rcount (0.511)> rtab (0.482) means that the hypothesis is accepted and there is a relationship between back muscle flexibility with volleyball service on the Pekanbaru AZZUHRA Junior High School team. Third analysis between shoulder arm muscle strength (x1) and back muscle flexibility (x2) and volleyball service on the azzuhra junior high school team (y) where rtab at a significant level α (0.05) = 0.482 means, r count (0.628)> rtab (0.482), and rtab at a significant level α (0.05) = 0.482 means r count (0.511)> rtab (0.482) and rtab at the standard level significant α (0.05) = 0.482 means rhit (0.631)> rtab (0.482). Then it can be concluded that the relationship between (x1), (x2), and (y) or the relationship between the strength of the shoulder arm muscles and back flexibility with servicing on volleyball on the Pekanbaru Azzuhra Junior Team.Key Words: Arm-Shoulder Muscle Strength, Back Muscle, Volleyball Service